Pelatihan pengujian Formalin dan Boraks pada makanan dengan Reaksi warna alami di Persatuan Wirid Batak Islam (PWBI) Kelurahan Kwala Bekala Medan - Supiyani, Supiyani; Rahayu, Yayuk Putri; Nasution, Haris Munandar; Hizbullah, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
In an effort to improve public health by reducing the use of hazardous food additives in the city of Medan, community service has been carried out at the Perwiritan Batak Islam (PWBI) in Kwala Bekala, Medan Johor, Medan city on December 19-20, 2024. The training focused on learning how to test for formalin and borax in food using the natural color reaction of turmeric and KMnO4 (blue medicine) with 18 participants. This activity contributed to enhancing the technical skills of testing for formalin and borax to prevent and reduce the risk of using hazardous food additives. After this training, participants' knowledge about natural color tests on food containing formalin and borax improved. Pre-test and post-test evaluations of 20 participants showed a significant improvement in their understanding, with evaluation graphs indicating a shift from a low level of knowledge to a better level of knowledge.